A short easy test can detect ability for autonomous insulin injection by the elderly with diabetes mellitus - Zeyfang, Andrej; Oster, Peter; Bahrmann, Anke (Journal of the American Medical Directors Association, 2012)
Objective - Elderly patients with diabetes often have difficulty with self-administering insulin. It was the aim of the present study to find a short, easy performance test, such as the Timed Test of Money Counting (TTMC), that identifies elderly patients with diabetes, in grade to undertake proper insulin injection autonomously and correctly. - Patients and Methods - A total of 73 insulin-dependent patients (age 77.3 ± 7.1 years, HbA1c 8.2% ± 2.0%) completed the TTMC as part of a comprehensive geriatric assessment before and 3 months after structured diabetes education. - Results - The TTMC showed a sensitivity of 69.2% for autonomous injection of insulin 3 months after diabetes education, if patients performed the test within a time duration of less than 46 seconds. Specificity is 70% and positive predictive value 78.7% in this case. - Study Implication - The TTMC seems to be a suitable predictor for ability to inject insulin autonomously after receiving diabetes education. The expenditure of time is only about 5 minutes and it helps to identify patients with diabetes who are able to inject insulin themselves after diabetes education.